Investigating the influence of insulin on autophagy induction and autophagic turnover in mycobacterium tuberculosis-infected macrophages - Scholtz, Denise (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.